2011
DOI: 10.1016/j.neuron.2011.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Associative Cortex Features in the First Olfactory Brain Relay Station

Abstract: Summary Synchronized firing of mitral cells (MCs) in the olfactory bulb (OB) has been hypothesized to help bind information together in olfactory cortex (OC). In this first survey of synchronized firing by suspected MCs in awake-behaving vertebrates we find the surprising result that synchronized firing conveys information on odor value (is it rewarded?) rather than odor identity (what is the odor?). We observed that as mice learned to discriminate between odors synchronous firing responses to the rewarded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
178
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(193 citation statements)
references
References 59 publications
(104 reference statements)
15
178
0
Order By: Relevance
“…The authors suggest that this is an easily understood and implemented population temporal code, the decoding of which simply requires downstream coincidence detectors, connected to decision-making networks, that take input from both members of the neuron pair. Doucette et al (2001) then found that the SS rate is modulated by noradrenergic input to the bulb. In this way the SS code can signal the reinforcement significance of the stimulus.…”
Section: The Saliency Detection Hypothesismentioning
confidence: 98%
See 3 more Smart Citations
“…The authors suggest that this is an easily understood and implemented population temporal code, the decoding of which simply requires downstream coincidence detectors, connected to decision-making networks, that take input from both members of the neuron pair. Doucette et al (2001) then found that the SS rate is modulated by noradrenergic input to the bulb. In this way the SS code can signal the reinforcement significance of the stimulus.…”
Section: The Saliency Detection Hypothesismentioning
confidence: 98%
“…This detailed arrangement suggested to Rahman and Baizer (2007) that many claustral neurons make extensive inter cell type and intraclaustral connections. These connections between the GABAergic network and the INs in the CDNN may serve to allow many modulatory functions as to the fine tuning of the CDNN by neuromodulators, such as norepinephrine and others (Doucette et al, 2001).…”
Section: The Role Of Gabaergic Interneuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Memory for the conditioning odor is likely to be represented as a stronger, sharper, and more synchronized mitral cell output from the olfactory bulb. An increased output synchrony has recently been shown to indicate encoded reward (Doucette et al 2011). g frequency enhancement by the a 2 -adrenoceptor may confer the reward signature in odor preference learning.…”
mentioning
confidence: 99%